A new revenue model: a different approach to reduce music piracy. (18th July 2011) - Midha, Vishal; Ahluwalia, Punit; Hughes, Jerald
There is no evidence that various proposed technological barriers have been effective in stopping music piracy. Different studies have proposed either anti-piracy or pro-piracy ways to solve the music industry's problems, but piracy still exists. In this paper, we build a mathematical model of a new revenue model which the music industry could implement in order to curb piracy. Our findings suggest that music industries should incorporate versioning of their products to target different types of consumers. Additionally, our analysis shows that by using this approach, the music industry cannot only reduce piracy but also increase revenues.